2019
DOI: 10.3390/genes10010069
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Sequencing and Hybrid Assembly of the Biofuel Crop Jatropha curcas L.: Identification of Quantitative Trait Loci for Geminivirus Resistance

Abstract: Jatropha curcas is an important perennial, drought tolerant plant that has been identified as a potential biodiesel crop. We report here the hybrid de novo genome assembly of J. curcas generated using Illumina and PacBio sequencing technologies, and identification of quantitative loci for Jatropha Mosaic Virus (JMV) resistance. In this study, we generated scaffolds of 265.7 Mbp in length, which correspond to 84.8% of the gene space, using Benchmarking Universal Single-Copy Orthologs (BUSCO) analysis. Additiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…The C. chinensis genome assembly was annotated via the following approaches: homology-based, transcriptome-based, and ab initio annotation. Thirteen representative species were selected to perform homology annotation, including Manihot esculenta (M. esculenta) 48 , Populus euphratica (P. euphratica) 49 , Populus alba (P. alba) 50 , Jatropha curcas (J. curcas) 51 , Ricinus communis (R. communis) 52 , Hevea brasiliensis (H. brasiliensis) 53 , Arabidopsis thaliana (A. thaliana) 54 , Cucurbita pepo (C. pepo) 55 , Fragaria vesca (F. vesca) 56 , Malus domestica (M. domestica) 57 , Populus trichocarpa (P. trichocarpa) 52 , Pyrus x bretschneideri (P. bretschneideri) 58 and Rosa chinensis (R. chinensis) 59 . The protein sequences of these species were aligned to C. chinensis genome sequences using TBLASTN software 60 with an E-value ≤ 1e-5.…”
Section: Genome Annotationmentioning
confidence: 99%
“…The C. chinensis genome assembly was annotated via the following approaches: homology-based, transcriptome-based, and ab initio annotation. Thirteen representative species were selected to perform homology annotation, including Manihot esculenta (M. esculenta) 48 , Populus euphratica (P. euphratica) 49 , Populus alba (P. alba) 50 , Jatropha curcas (J. curcas) 51 , Ricinus communis (R. communis) 52 , Hevea brasiliensis (H. brasiliensis) 53 , Arabidopsis thaliana (A. thaliana) 54 , Cucurbita pepo (C. pepo) 55 , Fragaria vesca (F. vesca) 56 , Malus domestica (M. domestica) 57 , Populus trichocarpa (P. trichocarpa) 52 , Pyrus x bretschneideri (P. bretschneideri) 58 and Rosa chinensis (R. chinensis) 59 . The protein sequences of these species were aligned to C. chinensis genome sequences using TBLASTN software 60 with an E-value ≤ 1e-5.…”
Section: Genome Annotationmentioning
confidence: 99%
“…Hybrid assembly offers several advantages over de novo assembly solely using short or long reads. For instance, hybrid assembly makes the downstream analyses, mapping, and annotation of genomic features more accurate [16]. Furthermore, it has been shown that hybrid assembly provides a better resolution for studying tandem repeats as well as gene variants [17], and it is the ideal approach for predicting the plasmids and AMR genes [13].…”
Section: Introductionmentioning
confidence: 99%
“…The leaf curl disease in Jatropha, caused by the whitefly transmitted geminiviruses, is the most devastating. In India, it causes a reduction of up to 80% in seed yield 11 and 40% in oil production 12 . The symptoms of the disease include mosaic and curling of leaves and malformed fruits.…”
Section: Introductionmentioning
confidence: 99%